2006
DOI: 10.1186/1471-2334-6-101
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C: prevalence and risk factors associated with seropositivity among children in Karachi, Pakistan

Abstract: BackgroundInfections with hepatitis B virus (HBV) and hepatitis C virus (HCV) can lead to chronic liver disease and hepato-cellular carcinoma (HCC). This cross-sectional study estimated the prevalence and identified risk factors associated with Hepatitis B surface antigen (HBsAg) and HCV antibody (anti-HCV) sero-positivity among children 1 to 15 years of age.MethodsThe study targeted the low to middle socioeconomic population that comprises 80% to 85% of the population. Consent was obtained from parents of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
95
5
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 14 publications
11
95
5
1
Order By: Relevance
“…It is also lower than that of 1% found in Pakistan 26 and of 4.3% in individuals from Thailand of a similar age range born before the implementation of the HBV vaccination, but similar to that of 0.7%, in those born afterwards 27 .…”
Section: Resultsmentioning
confidence: 54%
“…It is also lower than that of 1% found in Pakistan 26 and of 4.3% in individuals from Thailand of a similar age range born before the implementation of the HBV vaccination, but similar to that of 0.7%, in those born afterwards 27 .…”
Section: Resultsmentioning
confidence: 54%
“…Agboatwalla et al [20] , 1994 Karachi ELISA 236 0.44 Khan et al [21] , 1996 Lahore EIA,RIBA 538 4.09 Parker et al [22] , 1999 Lahore ELISA 538 1.30 Hyder et al [23] , 2001 Lahore ELISA 171 0.58 Jafri et al [24] , [25] ,…”
Section: Unsafe and Unnecessary Needlesmentioning
confidence: 99%
“…Ten different studies showed that the percent prevalence of HCV in the general adult population was 4.95% ± 0.53% [10][11][12][13][14][15][16][17][18][19] , while six studies showed a percent prevalence of 1.72% ± 0.24% in the pediatric population [20][21][22][23][24][25] . In Pakistan, military recruits are screened for HCV before induction; six different studies showed a percent prevalence of 3.64% ± 0.31% in candidates for military recruitment [26][27][28][29][30][31] .…”
Section: General Populationmentioning
confidence: 99%
“…A rate of 1.6% 17 was reported in Pakistani children aged between l-5years, and 0.4% 18 in American under 12s.The lower prevalence rates among the Pakistani and American children compared to findings in this study in newborns may be due to spontaneous resolution of some acute infections over time as documented in studies where children were followed up for long periods with resultant loss of HCV antibodies and negative viral antigen detection tests where earlier tests had been positive.…”
Section: Discussionmentioning
confidence: 99%